Computers Helping People with Special Needs 12th International Conference, ICCHP 2010, Vienna, Austria, July14-16, 2010, Proceedings, Part II - Miesenberger, Klaus; Klaus, Joachim; Zagler, Wolfgang; Karshmer, Arthur; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constiutes the proceedings of the 12th International Conference on Computers Helping People with Special Needs, held in Vienna, Austria, in July 2010.
People with Specific Learning and Cognitive Problems: ICT, AT and HCI -- People with Motor Disabilities: HCI and Rehabilitation -- People with Motor Disabilities: How to Improve Text Input -- Deaf and Hard of Hearing People: Accessible Information and Education -- Deaf People: AT for Sign Language -- Blind and Partially Sighted People: Mobility and Interaction without Sight -- Blind and Partially Sighted People: Rehabilitation and Social Skills -- Blind and Partially Sighted People: HCI -- Blind and Partially Sighted People: Access to Mathematics -- Blind and Partially Sighted People: Designing Haptic Interaction for a Collaborative World -- Blind and Partially Sighted People: Three-Dimensional Tactile Models for Blind People and Recognition of 3D Objects by Touch -- Ageing: HCI Usability (HCI4AGING).
Keywords: Computer science; Information systems; Multimedia systems; Computer vision; Education; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Computers and Society; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Computers and Education